MENGIDENTIFIKASI PERSEPSI MASYARAKAT PEMULUNG LUBUK MINTURUN KECAMATAN KOTO TANGAH TERHADAP PENDIDIKAN FORMAL WAJIB BELAJAR 12 TAHUN - Tricilia Agustina; Syamsir; Annisa; Ramayani Putri; Rifki; Yoana Alexandra (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to determine the perceptions of scavengers towards formal 12-year compulsory education. This case study is at the Lubuk Minturun TPA. This research belongs to the type of qualitative descriptive research. Data collection techniques in this study are observation, interviews, and documentation. As well as data processing using the stages of problem formulation, data collection, data analysis, and report writing. The results of this study indicate that the Lubuk Minturun TPA scavenger community has a negative perception of the 12-year compulsory formal education. It has been found through the results of research that many scavengers do not send their children to school because there is no money. They prefer their children to work to make money. The obstacle faced by scavengers is limited income, which makes it difficult to support education for their children who are 12 years of school.